Validity and reliability of a Food Frequency Questionnaire (FFQ) assessing food groups consumption and nutrients intake in Costa Rican adolescents - Monge-Rojas, Rafael; Alvarado-Barrantes, Ricardo; Vargas-Quesada, Rulamán; Chinnock, Anne (Población y Salud en Mesoamérica, 2024)
Introduction: Food Frequency Questionnaires (FFQ) have been widely used in several age groups, including adolescents, due to their greater advantages over other dietary measurement methods. Therefore, this study was designed to assess the validity and reliability of a FFQ designed for use on Costa Rican adolescents. Methodology: The validation and reproducibility studies were carried out in a sample of 107 adolescents of San José province selected through convenience sampling. For validation, a comparison of the nutrient intake and food consumption data obtained with the FFQ was made with those derived from the 3-day food record (3FR). Reliability was assessed by comparing nutrient intake and food consumption derived from the first FFQ with another FFQ performed four weeks after the first. Results: FFQ overestimates 3FR, with an average overestimation of 40.2% for foods and 38.8% for nutrients. The cross-classification was good for 24 of 26 nutrients and for 12 of the 21 food groups, and the weighted kappa showed an acceptable discriminant ability of the FFQ to categorize individuals into broad nutrient intake (except for protein and cholesterol) and food groups categories (dairy products, white rice, beans, vegetables, fruits and fruit juice, sugary drinks, breakfast cereal, candies and sweets, snacks, fast foods, fat, and ice cream). Conclusions: The FFQ designed for Costa Rican adolescents was unable to assess absolute dietary intakes; however, it is a reasonable tool to categorize adolescents into broad ranges of dietary intakes and could be used to evaluate dietary patterns in epidemiological studies of diet-disease associations.